2018
DOI: 10.1002/ejic.201701404
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Carbon Dioxide Capture and Cooperative Catalysis of a Water‐Stable Acylamide‐Functionalized Metal–Organic Framework

Abstract: Incorporation of specific functionalities within the framework offers a significant opportunity to produce high-performance gas storage/separation and catalysis MOF materials. In this work, multifunctionalities, including hydrophobic methoxy groups, polar acylamide functionalities, and open copper(II) sites, have been successfully integrated into a twofold interpenetrated microporous MOF (HNUST-6, HNUST represents Hunan University of Science and Technology). HNUST-6 possesses per- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…The NMR analysis data clearly revealed that the pure product (ethyl 6-methyl-2-oxo-4-phenyl-3,4-dihydro-1H-pyrimidine-5-carboxylate) could be synthesised from benzaldehyde, ethyl acetoacetate and urea using the coordination polymers as reaction catalysts. The spectral data of the obtained Biginelli product (ethyl 6-methyl-2-oxo-4-phenyl-3,4-dihydro-1H-pyrimidine-5-carboxylate) are the following: 1 The yields of the products of heterogeneous catalysis using the synthesised hybrid organic-inorganic compounds are displayed in 3 •DMF agglomerates showed an evident tendency of transformation to hexagonic crystallites. Therefore, we can conclude that the catalytic activity of the synthesised hybrid organic-inorganic compounds was very dependent on the surface microstructure of these hybrid materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMR analysis data clearly revealed that the pure product (ethyl 6-methyl-2-oxo-4-phenyl-3,4-dihydro-1H-pyrimidine-5-carboxylate) could be synthesised from benzaldehyde, ethyl acetoacetate and urea using the coordination polymers as reaction catalysts. The spectral data of the obtained Biginelli product (ethyl 6-methyl-2-oxo-4-phenyl-3,4-dihydro-1H-pyrimidine-5-carboxylate) are the following: 1 The yields of the products of heterogeneous catalysis using the synthesised hybrid organic-inorganic compounds are displayed in 3 •DMF agglomerates showed an evident tendency of transformation to hexagonic crystallites. Therefore, we can conclude that the catalytic activity of the synthesised hybrid organic-inorganic compounds was very dependent on the surface microstructure of these hybrid materials.…”
Section: Resultsmentioning
confidence: 99%
“…The assembly of multifunctional ligands with metal ions is currently of great interest due to their use in constructing two-and three-dimensional polymers with special properties, such as electrical conductivity, magnetism, host-guest chemistry, catalysis and luminescence [1][2][3][4]. Reactions of Me x+ NO 3 • yH 2 O (Me x+ = Fe 3+ , Ni 2+ , Mn 2+ , Co 2+ ) with respectively 4-nitrosalycilic (4NSA) and acids [5] produced hybrid organic-inorganic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Natural gas distributed energy systems produce almost no solid waste, which eases the burden of urban waste treatment. Water pollution caused by electricity reached about 2 billion cubic meters [52]. Several worldwide environmental conferences mentioned worsening situations of water pollution.…”
Section: Strengthsmentioning
confidence: 99%
“…In the past two decades, enormous progress has been made in the synthesis and application of MOFs [3,4,5]. Because of their remarkable structural features, such as high porosity and large surface area, as well as their exceptional physicochemical properties, MOFs possess versatile applications in gas storage and separation [6,7,8,9,10,11], heterogeneous catalysis [12,13,14,15], drug delivery and chemotherapy [16,17], and sensing [18,19]. As new types of promising functional materials, luminescent MOFs especially have great potential as alternative phosphors in lighting devices and luminescent sensors [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%